Risk factors for prolonged recovery from concussion in young patients. Issue 23 (14th September 2022) - Cuff, Steven; Maki, Aaron; Feiss, Robyn; Young, Julie; Shi, Junxin; Hautmann, Amanda; Yang, Jingzhen
Abstract : Objectives: For young patients sustaining concussion, assessing recovery is vital in determining safe return to play. Identifying risk factors may aid clinicians in recognising patients at risk for prolonged recovery. The study objective is to identify risk factors for prolonged (>28 days) and extended (>90 days) recovery (defined as symptom duration) and analyse how these risk factors differ between the two groups. Methods: We retrospectively analysed electronic health record data (n=4937) among patients aged 10–18 years collected at Nationwide Children's Hospital Sports Medicine concussion clinics between 1 July 2012 and 30 June 2019. Data collected included patient demographics, comorbidities (eg, prior psychiatric diagnoses, prior concussions) and injury characteristics (eg, loss of consciousness, injury setting). We examined patient risk factors for prolonged (>28 days) and/or extended (>90 days) recovery using modified Poisson regression models. Results: Factors associated with increased risk of prolonged recovery from concussion included prior concussions (adjusted risk ratio (ARR) 1.19, 95% CI 1.02 to 1.38) for two concussions (ARR 1.36, 95% CI 1.14 to 1.61), for >3, and higher initial symptom score (ARR 2.57, 95% CI 2.34 to 2.83) for postconcussion symptom (PCS) scores 21–60 (ARR 2.89, 95% CI 2.54 to 3.29), for PCS>60. Risk factors for extended recovery included history of concussion (ARR 1.50, 95% CI 1.09 to 2.06) for two concussions (ARR 1.75, 95% CI 1.17 to 2.62), for >3 and older age (15–18 years, ARR 1.11, 95% CI 1.05 to 1.18). Additionally, comorbid attention deficit hyperactivity disorder increased risk of prolonged recovery (ARR 1.14, 95% CI 1.01 to 1.29) while anxiety increased risk for extended recovery (ARR 1.47, 95% CI 1.10 to 1.95). Conclusion: Overall, risk factors for prolonged recovery differ somewhat from risk factors for extended recovery. For patients who present to clinic with concussion, mental health is an important consideration which may impact the timeline for symptom recovery.